BEHAVIOR OF MICROPILE FOUNDATIONS UNDER INCLINED LOADS IN LABORATORY TESTS - G. - L. You; K. Miura; M. Ishito (Lowland Technology International, 2003)
Subsequent to the model investigation of the load bearing mechanism of micropile foundations in sand under vertical loads, this model study aims to further investigate the load bearing behavior of micropile foundations under inclined loads in sand. Three series of model tests (footing, micropile, and micropile foundation tests, respectively) are conducted in very dense sand (Dr = 95 ± 3%) under three different load inclinations (k = Ph/P = 0.3, 0.6, and 0.9, respectively). The test results under inclined loads are comparatively analyzed using the results of the vertical loading tests (k =0.0), and discussed in terms of displacements, coefficients of subgrade reaction, and the network effect index. It is found that micropiles can effectively improve the bearing capacity of surface footings under inclined loads. However, as expected, the improvement of bearing capacity decreases with the load inclination. A positive network effect is observed in the model tests under inclined loads as in the vertical loading tests in previous studies. The network effect index, R increases gradually with settlement under different load inclinations; at a large settlement, a network effect index of 1.2 is obtained in inclined loading tests. It is found that the footing in the early loading stage tends to move toward the vertical direction in the footing tests under inclined loads, while the opposite results are observed in the micropile tests. The vertical coefficient of subgrade reaction of micropile foundations is higher than those of footings and micropiles, and its horizontal coefficient is more than twice of that of micropiles at k = 0.3. This indicates that the surface footing not only plays a role in load bearing, but also makes a remarkable contribution in positively mobilizing the interaction among footing, micropiles, and subsoil. The bearing capacity of micropile foundations is larger at small battered angles of micropiles under inclined loadings, and it decreases at large battered angles. Consequently, the coefficient of vertical subgrade reaction decreases with the battered angle in micropile foundation tests. On the other hand, the horizontal coefficient increases with the battered angle up to 45°.